Perspektif Sastra Bandingan dan Antropologi dalam Novel Bumi Manusia dan Ulysses - Ibrahim, Prasasri; Bagtayan, Zilfa Achmad (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
The literary world offers a variety of works that introduce different views on life, social conflicts, and cultural dynamics. Two great literary works that are not only important in the history of their countries' literacy, but also make major contributions to global literary discourse. This study examines the relationship between two great literary works, Bumi Manusia by Pramoedya Ananta Toer and Ulysses by James Joyce, through a comparative literature approach. Both novels depict the struggle for individual identity in different social contexts: Dutch colonialism in Indonesia and modern Dublin society in the early 20th century. Bumi Manusia highlights Minke's struggle to find an indigenous identity amidst colonial oppression, while Ulysses explores Leopold Bloom's alienation in the seemingly monotonous routine of life. Through thematic, structural, and cultural analysis, this study shows the differences in narrative techniques of the two novels, with Bumi Manusia using a linear plot and Ulysses being more complex with a stream of consciousness. Despite their different cultural and historical backgrounds, both novels reflect the search for identity and social challenges that are relevant to their contexts. This comparative literature approach provides new insights into understanding the dynamics of human identity in their respective social, political, and cultural contexts.